Visual impairment due to retinopathy of prematurity (ROP) in New Zealand: a 22-year review. Issue 6 (19th December 2014) - Tan, Zachary; Chong, CheeFoong; Darlow, Brian; Dai, Shuan
Abstract : Aim: To evaluate retinopathy of prematurity (ROP)-related visual impairment in New Zealand children. Methods: 22-year retrospective review of medical records of children with moderate to severe visual impairment registered with the Blind and Low Vision Education Network New Zealand. The cohort was divided into two periods (1991–2004; 2005–2012) for analysis. Results: 232 children with ROP were treated in the study period (109 in period 1, 123 in period 2). 36 children, 63.9% of whom were of male sex, were identified with subsequent significant visual impairment (27 in period 1, 9 in period 2). The incidence of new cases of visual impairment from ROP declined from 271.6 infants/100 000 live very preterm births per annum (period 1) to 146.1 per annum (period 2). Mean gestational age and mean birth weight were comparable between the two study periods. 75% of children with visual impairment from ROP received treatment for their condition (period 1, 74.1%; period 2, 77.8%) and modalities used changed significantly over time. The modal visual outcome overall was Snellen visual acuity <6/18–6/60 (55.6%) (period 1, 51.9%; period 2, 66.7%). The proportion of children with no light perception bilaterally decreased over time (period 1, 3.7%; period 2, 0%). Conclusions: There has been a reduction in the incidence of infants with significant visual impairment from ROP over time in New Zealand, likely due to progress in clinical management of ROP. Our study suggests the current ROP screening criteria of <31 weeks' gestation or <1250 g are of sufficient breadth.